2004
DOI: 10.1248/bpb.27.1174
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Function of Calcium-Independent Phospholipase A2

Abstract: The catalytic activity of calcium-independent phospholipase A 2 (iPLA 2 ), which is classified as a group VI PLA 2 , is regulated by protein kinase C, calmodulin, and others such as reactive oxygen species. Numerous findings have shown that iPLA 2 is involved in stimulus-induced arachidonic acid release and lysophospholipid generation, although the participation is dependent upon the cell type and stimulus. The catalytic action of iPLA 2 is known to be responsible for phospholipid remodeling as a housekeeping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
1
5

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 58 publications
2
86
1
5
Order By: Relevance
“…AA release depends on ␤-cell metabolism of glucose (76), and it has been shown that exogenous AA is capable of causing a rise in cytosolic Ca 2ϩ (77). Importantly, AA is substrate for the synthesis of eicosanoid signaling molecules (78). Lysophosphatidic acids, produced in addition to AA by the action of phospholipase A isoforms on membrane phospholipids, also have signaling actions (78).…”
Section: Aa Signaling and Phospholipase Amentioning
confidence: 99%
See 2 more Smart Citations
“…AA release depends on ␤-cell metabolism of glucose (76), and it has been shown that exogenous AA is capable of causing a rise in cytosolic Ca 2ϩ (77). Importantly, AA is substrate for the synthesis of eicosanoid signaling molecules (78). Lysophosphatidic acids, produced in addition to AA by the action of phospholipase A isoforms on membrane phospholipids, also have signaling actions (78).…”
Section: Aa Signaling and Phospholipase Amentioning
confidence: 99%
“…Importantly, AA is substrate for the synthesis of eicosanoid signaling molecules (78). Lysophosphatidic acids, produced in addition to AA by the action of phospholipase A isoforms on membrane phospholipids, also have signaling actions (78). Although it was thought that glucose-stimulated AA release is from hydrolysis of membrane phospholipids (75)(76)(77)(78)(79), another possibility is that it is from hydrolysis of TG within the TG/FFA cycling pathway.…”
Section: Aa Signaling and Phospholipase Amentioning
confidence: 99%
See 1 more Smart Citation
“…cPLA 2 preferentially cleaves ArAc at the sn-2 position of PC and forms lyso-PC, whereas sPLA 2 s show no fatty acid preference and act on a broader range of phospholipids (45,46). iPLA 2 s also are not selective for ArAc and are considered to be involved primarily in membrane remodeling (47,48). Full activation of cPLA 2 requires binding of Ca 2+ for translocation from cytosol to the phospholipid membrane and phosphorylation of specific serine residues (49).…”
Section: Pc Hydrolysis By Phospholipasesmentioning
confidence: 99%
“…Among the PLA 2 s is an 85 kDa cPLA 2 that requires Ca 2+ for catalysis, and a calcium independent PLA 2 , iPLA 2 β, for which several potential functions have been proposed, including a housekeeping role in phospholipid remodeling and a signaling role in cell growth, apoptosis, secretion, inflammation, and oxidant-induced cell injury (Chakraborti, 2003). A number of observations that iPLA 2 has a functional role in cellular signaling in addition to its roles in AA release and phospholipid remodeling have been reported (Akiba & Sato, 2004). iPLA 2 mediates the phosphorylation of transcription factors through a PKAdependent pathway (Martinson et al, 2003).…”
Section: Phospholipase a 2 Activationmentioning
confidence: 99%